The Fundamental Research Inspiration in Fashion Design - Muhammad Khalik Mustafa; Nasyirah Saleh; Dayang Intan Farahanies; Mohd Radzuan Mohd Rafee; Ishak Ramli; Muhammad Redza Rosman (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This study explores the fundamental role of inspiration in the field of fashion design, highlighting its influence in integrating functionality, aesthetic expression, and responsiveness to ever-evolving trends. Fashion design is not merely about creating garments; it is a dynamic process that demands a balance between artistic vision and practical innovation. The research investigates a wide range of inspiration sources, such as nature, fine art, cultural heritage, personal experiences, and emerging technological advancements. These sources are critically examined for their ability to shape a designer’s conceptual thinking, fuel originality, and support the forecasting of trends. A key focus is given to distinguishing between tangible sources such as objects, environments, and physical stimuli and intangible sources, including emotions, memories, and abstract ideas. The study reveals how these diverse inspirations contribute to the richness and multidimensional nature of contemporary fashion design. By understanding how designers interpret and translate inspiration into design elements, the research provides a framework for appreciating the creative process. Moreover, it underscores the importance of inspiration not only as a spark for creativity but also as a tool for strategic problem-solving and innovation. This study ultimately emphasizes the interplay between inspiration, creativity, and decision-making within the modern fashion design landscape. Keywords: Fashion Design Inspiration, Creative Process, Trend Forecasting